Customer capabilities, switching costs, and bank performance - Brush, Thomas H.; Dangol, Ramesh; O'Brien, Jonathan P. (Strategic Management Journal, 2012)
Abstract Customers develop switching costs when they invest time and effort to develop capabilities required to optimally use a given product. Such capabilities are likely to be firm specific and cannot be transferred perfectly to competitors' product offerings. Customers who face switching costs are likely to remain with the same firm and consume complementary products that meet their needs. Thus, firms can achieve competitive advantage by exploiting customers' switching costs. In this paper, we hypothesize that the extent to which firms can benefit from customers' switching costs is contingent upon the firms' internal cross‐selling capabilities. We use online banking data to test our hypotheses and find that customers' switching costs contribute to banks' profitability only in the presence of high levels of internal cross‐selling capabilities. Copyright © 2012 John Wiley & Sons, Ltd.